Taking travel home : The souvenir culture of British women tourists, 1750-1830 - Gleadhill, Emma (Book collections on Project MUSE., 2022)
This book provides a new cultural history of the travel souvenir. It uncovers how eighteenth-century British women enlisted the objects they collected during their European travels to realise their ambitions in the arenas of connoisseurship, science and friendship, and to stake their claims to agency and authority as travelling subjects.